Penerapan Prinsip Transparansi Dalam Pelayanan Publik (Studi Pada Dinas Kependudukan Dan Pencatatan Sipil Kota Kendari) - Alimudin, Alimudin; Jopang, Jopang; Aminuddin, Aminuddin (Universitas Halu Oleo, 2020)
This study aims to describe the implementation of the principle of transparency in public services at the Department of Population and Civil Registration of Kendari City. The method used in this research is a descriptive qualitative method by means of observation, interviews and documentation. The results of this study indicate that the application of the principle of transparency in public services at the Kendari City Population and Civil Registry Service is generally good which includes 5 indicators, namely procedures, officers or authorized officials, service promises, reliability, and responsiveness. although there are still 3 indicators that are missing. satisfying namely belief, empathy, and tangibility. In addition, public services at the Kendari City Population and Civil Registration Service are still not optimal, especially the problem of timeliness.